Stress lines inspired structural patterns for tall buildings. (15th February 2021) - Cascone, Francesco; Faiella, Diana; Tomei, Valentina; Mele, Elena
Highlights: Proposal of diagrid tall building patterns mimicking the principal stress lines. Diagrid tall building models characterized different slenderness ratios are analysed. The patterns are evaluated in terms of structural weight and structural performance. Abstract: In this paper, an innovative diagrid-like pattern for tall building structures is proposed. Based on the concept of principal stress trajectories, the pattern is characterized by triangular units with angle varying along width and elevation, and, being the expression of forces flow arising in the building façades, it is expected to be highly efficient and visually appealing. The idea is to model the building as a three-dimensional vertical cantilever beam with tubular section under horizontal load, and to derive the relevant principal stress lines. Then, the stress analysis results are processed, and geometrical rules are derived for generating structural grids that also satisfy constructability constraints. For this purpose, a framework for implementing and managing the stress lines concept in the preliminary structural design of tall buildings is proposed. The efficacy of the generation procedure and the efficiency of the obtained structural patterns are then verified by means of the application to tall building models characterised by different slenderness ratios, and by means of comparisons with the performance and steel weight of conventional diagrid structures.